MANAJEMEN PEMERINTAH KOTA PEKANBARU DALAM PENYEDIAAN RUANG TERBUKA HIJAU PUBLIK TAMAN KOTA DI KOTA PEKANBARU TAHUN 2018 - Dwi Sapto Anggoro; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
According to Law Number 26 of 2007, Green Open Space (Ruang Terbuka Hijau) concerning Spatial Planning is an elongated area or lane and / or group, which is more open as a place to grow plants, whether grown naturally or intentionally planted. The existence of Green Open Space is one of the important elements in forming a comfortable and healthy city environment. The city of Pekanbaru has an area of 632.26 km2 with a population in 2018 of 1,064,566 people. Guided by the Minister of Public Works Regulation Number 05 / PRT / M / 2008, Pekanbaru City has at least a city park with an area of 319,369 m2 with a minimum area / capita of 0.3 m2. If adapted to existing regulations, ideally Pekanbaru City must have 2 to 3 city parks with an area of 144,000 m2 / unit.The purpose of this study is to determine the extent of the management of Pekanbaru Government in the procurement of City Parks in Pekanbaru City in 2018, as well as obstacles that hinder the process of procuring city parks in Pekanbaru City. The type of research used is qualitative research methods. The location of this research was conducted at the Public Works and Spatial Planning Office of Pekanbaru City. The technique of data collection is done by completing information through interviews and documentation asking for the data needed to the agency to be studied. While data analysis is done using qualitative analysis methods.Based on the results of the study, the author concluded that the management of the city of Pekanbaru in the procurement of city parks is still constrained by the weak law enforcement due to the absence of specific regional regulations. Besides, there’s more other problem such as land acquisition that will be used as a city park area is also still the main problem of the Pekanbaru City Government, as well as the many changes in the conversion of open land into built-up land.Keywords: Planning, Policy, City Park